The Development of Sport Scientific Research: A Bibliometric Analysis - Saputra, Sylvana Yaka; Isnaini, Lalu Moh Yudha; Allsabah, Muhammad Husein (Indonesian Journal of Sport Management, 2024)
The purpose of this study is to analysis research trends with Sport Development keywords that have been published in reputable international journals indexed by Scopus by visualizing meta data with bibliometric analysis using the VOSviewer application. This research data is a scientific article collected on July 20, 2023 with the keyword Sport Development time span 2019-2023 on the Scopus databese. Research on Sport Development in the period 2019-2023 on the Scopus database decreases every year. In 2019 there were 75 articles, in 2020 there were 54 articles, in 2021 there were 38 articles, in 2022 there were 28 articles and in 2023 there was 1 article. Based on bibliometric analysis using VOSviewer, the data cluster on the sport development keyword is divided into 4 clusters. In cluster 1, topics and themes related to research concepts with a focus on case study, effect, and woman, cluster 2 focuses on health, sport industry, and sustainable development, cluster 3 focuses on learning, physical education, professional development and finally cluster 4 focuses on positive youth development, and youth sport.